Cálculo dos Coeficientes de Conversão para Dose Equivalente e Dose Efetiva em termos da Fluência para Nêutrons utilizando simulador antropomórfico UFHADF em diferentes posturas e o código MCNPX - Matos Neto, Antonio (2014)
The protection of occupational workers and public to the harmful effects of ionizing radiation is important for preventing and limiting the risks to the health of these individuals. The limitation of radiation dose is given by protection quantities, equivalent and effective doses (and), which are not directly measured but can be estimated by conversion coefficients, which relates them with physical quantities such as fluence ( ). Due to the difficult implementation of invasive techniques for estimating radiation dose in humans, the development of computational simulators representing more realistic as possible the structures of human body provides a more accurate dose estimation of individuals exposed to radiation. In literature, the significant growing of works in estimating conversion coefficients are observed, however using exposure scenarios that the computational simulators are implemented in standing posture. The aim of this work was the calculation of conversion coefficients for equivalent and effective doses per fluence (E/ e H/) of sitting and standing female simulators irradiated by neutrons. The exposure scenarios were developed using the UF sitting and standing female simulators implemented on MCNPX radiation transport code, which simulating a plane source of monoenergetic neutrons with energies from 10-9 MeV to 10 GeV in antero-posterior (AP), postero-anterior (PA), right lateral (RLAT), left lateral (LLAT), rotational (ROT) and isotropic (ISO) irradiation geometries. The conversion coefficients calculated in this work showed significant differences in organs of pelvic region of simulator for AP, LLAT, ROT and ISO irradiation geometries, such as bladder (53,40% in ROT geometry), ovaries (77,04% in RLAT geometry) and uterus (56,20% in AP geometry). These results mainly occurred due the shielding of these organs by the legs of simulator in sitting posture, and the differences showed the relevance of calculating conversion coefficients of simulators in different postures, which are near to a real scenario of an individual exposed to radiation.